2018
DOI: 10.1111/mcn.12593
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition‐sensitive agricultural interventions and gender dynamics: A qualitative study in Nepal

Abstract: Undernutrition and low women's status persist as major development obstacles in South Asia and specifically, Nepal. Multi-sectoral approaches, including nutrition-sensitive agriculture, are potential avenues for further reductions in undernutrition. Although evidence is growing, many questions remain regarding how gender mediates the translation of agricultural production activities into nutritional benefit. In this study, we examined how gender influences the pathway from agricultural production to improved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Most of the studies reporting gender in their interventions examined the effects on women's empowerment without describing how the interventions influenced the underpinning gender dynamics that empowered women and consequently led to nutrition outcomes. Some other studies on underlying gender dynamics and NSA were excluded from this review because they did not report on nutrition outcomes ( 85 , 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reporting gender in their interventions examined the effects on women's empowerment without describing how the interventions influenced the underpinning gender dynamics that empowered women and consequently led to nutrition outcomes. Some other studies on underlying gender dynamics and NSA were excluded from this review because they did not report on nutrition outcomes ( 85 , 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…In several contexts, it was noted that women face daily mobility challenges that can limit their access to markets and food. For example, Kjeldsberg et al (2018) find that woman's mobility was an important factor related to woman's empowerment in the context of a nutrition-sensitive agriculture project in Nepal. Other articles found a relationship between the mother's freedom of mobility and nutritional outcomes for mothers and children.…”
Section: Conceptualizing Gender In Food Environmentsmentioning
confidence: 99%
“…Chaturvedi et al (2016) find that in India, there was a correlation between the amount of time mothers spent with their children and their nutrition status. Time constraints also impacted women's participation in an agriculture and nutrition program in Nepal (Kjeldsberg et al, 2018). And, Rafii et al…”
Section: Conceptualizing Gender In Food Environmentsmentioning
confidence: 99%
“…For young women living in the poorer households of LMICs, conditions are often particularly difficult in the absence of appropriate inexpensive and timely transport, as Venter et al demonstrated for rural South Africa and Esson et al for Accra, urban Ghana [70,79]. Cultural barriers to mobility vary (see Kjeldsberg et al regarding variations in rural Nepal [80]) but for some young married women, these barriers can be insurmountable, especially if they cannot find reliable transport for their return journey home. This tends to be particularly important because of consequent delays to evening meal preparations, possibly coupled with male suspicions of the reason behind their delay.…”
Section: Transport To Work For Young Womenmentioning
confidence: 99%